Effects of interleukin-1 receptor antagonism in women with polycystic ovary syndrome—the FertIL trial - Wälchli-Popovic, Milica; Monnerat, Sophie; Taylor, Angela E.; Gilligan, Lorna C.; Schiffer, Lina; Arlt, Wiebke; Vogt, Deborah R.; De Geyter, Christian; Hutter, Nina; Donath, Marc Y.; Sartorius, Gideon; Christ-Crain, Mirjam (Frontiers in Endocrinology, 2024)
Introduction Chronic low-grade inflammation might contribute to hyperandrogenaemia and metabolic complications in polycystic ovary syndrome (PCOS). The proinflammatory cytokine Interleukin (IL) 1 stimulates androgen production from ovarian cells, whereas blockade of the IL 1 pathway improves cardiometabolic health. We aimed to investigate whether blocking the IL 1 pathway ameliorates hyperandrogenaemia in patients with PCOS. METHODS This is a prospective, interventional, single-arm, proof-of-concept trial performed at a tertiary Hospital in Switzerland (08/2018 to 07/2020) in 18 premenopausal women with a diagnosis of PCOS according to Rotterdam criteria, total testosterone levels ≥ 1.7 nmol/l and C-reactive protein (CRP) ≥ 1.0 mg/l. Patients received 100 mg/day of the IL-1-receptor antagonist anakinra for 28 days and underwent weekly blood sampling until one week after end of treatment. The primary endpoint was the change in serum androstenedione levels on day 7 of treatment, assessed with liquid chromatography-tandem mass spectrometry. Seven of these women participated in a subsequent observational sub-study (05/2021 to 12/2021). RESULTS Median [IQR] androstenedione increased by 0.5 [-0.1, 1.6] nmol/l (p=0.048) with anakinra and by 1.3 [0.08, 2.4] nmol/l [p=0.38] without anakinra between baseline and day 7. Anakinra reduced CRP levels on days 7, 21 and 28 (p<0.001) but did not lead to an absolute reduction in androgens. However, 4 of 6 patients (67%) had smaller areas under the curves for androstenedione and/or testosterone during the 28-day intervention with anakinra as compared to 28 days without treatment. DISCUSSION Our findings suggest that anakinra suppresses IL-1-mediated chronic low-grade inflammation in PCOS and might attenuate biochemical hyperandrogenaemia.